Pediatric nursing consultation in the perspective of nurses from the family health strategy - Roberta Fernandes Gasparino; Janete Pessuto Simonetti; Vera Lúcia Pamplona Tonete (Universidade Federal do Ceará, 2014)
Qualitative study that analyzed conceptions and experiences of nurses about the pediatric nursing consultation and its systematization in the Family Health Strategy. Semi-structured interviews were recorded with ten nurses from four cities of the countryside of São Paulo, in 2011. The interviews were analyzed according to the method of Thematic Content Analysis, based on current assumptions of the systematization of nursing care and the comprehensive child health care. Generally, nursing consultations, and specifically, pediatric ones were defined as the nurses' activity that allows them to know the life/health story, current needs and prevent future problems, having recognized the importance of its implementation and systematization. The experiences reported the paucity and lack of systematization in the pediatric nursing consultation in the context studied. Processes of ongoing health education are necessary to ensure quality and completeness to children's health.